2021
DOI: 10.1038/s41467-020-20749-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and efficient perovskite quantum dot solar cells via hybrid interfacial architecture

Abstract: All-inorganic CsPbI3 perovskite quantum dots have received substantial research interest for photovoltaic applications because of higher efficiency compared to solar cells using other quantum dots materials and the various exciting properties that perovskites have to offer. These quantum dot devices also exhibit good mechanical stability amongst various thin-film photovoltaic technologies. We demonstrate higher mechanical endurance of quantum dot films compared to bulk thin film and highlight the importance of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
222
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(224 citation statements)
references
References 58 publications
(32 reference statements)
2
222
0
Order By: Relevance
“…[ 23–25 ] Concurrently, CsPbX 3 (X = Cl − , Br − , I − , or mixed‐halide) QDs with all‐inorganic crystal structures have emerged as a rising star for optoelectronic applications because of their stronger flexibility in adjusting the composition, optical and electrical properties, high photoluminescence quantum yields (PLQYs) due to impressive defect tolerance. Advances in CsPbI 3 QD solar cells have enabled high efficiency over 14%, [ 26–31 ] showing great potential for QD PVs. Although previous studies have demonstrated the promise of HSCs, none has demonstrated high PCEs over 15% in these hybrid devices, probably due to insufficient charge transfer and carrier extraction efficiencies at QD/organic hybrid heterointerfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23–25 ] Concurrently, CsPbX 3 (X = Cl − , Br − , I − , or mixed‐halide) QDs with all‐inorganic crystal structures have emerged as a rising star for optoelectronic applications because of their stronger flexibility in adjusting the composition, optical and electrical properties, high photoluminescence quantum yields (PLQYs) due to impressive defect tolerance. Advances in CsPbI 3 QD solar cells have enabled high efficiency over 14%, [ 26–31 ] showing great potential for QD PVs. Although previous studies have demonstrated the promise of HSCs, none has demonstrated high PCEs over 15% in these hybrid devices, probably due to insufficient charge transfer and carrier extraction efficiencies at QD/organic hybrid heterointerfaces.…”
Section: Introductionmentioning
confidence: 99%
“…a–d) Adapted with permission. [ 51 ] Copyright 2021, Springer Nature Limited. e–i) Adapted with permission.…”
Section: Pqd Solar Cell Architecturesmentioning
confidence: 99%
“…Lead halide perovskites have attracted considerable attention owing to their excellent characteristics such as solution processability, tunable bandgap, high charge carrier mobilities and high emission color purity [1][2][3][4][5][6][7][8][9][10][11][12]. They present promising potential in perovskite solar cells (PSCs) and light-emitting diodes (LEDs) over the past decade [13][14][15][16][17][18][19][20][21][22][23][24][25]. Currently, PSCs have reached power conversion efficiencies of over 25% in single-junction devices and the external quantum efficiencies (EQEs) of perovskite light-emitting diodes (PeLEDs) have reached more than 20%, being close to the state-of-the-art organic LEDs (OLEDs) [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%